The distribution distance of polycyclic aromatic hydrocarbons in the tundra zone under the impact of thermal power plant - Evgenia V. Yakovleva; Dmitriy N. Gabov (RUDN Journal of Ecology and Life Safety, 2019)
Being widely distributed in the tundra zone and highly sensible to temporal or spatial changes in composition of polycyclic aromatic hydrocarbons (PAHs) in ecosystems, Pleurozium schreberi Brid. can serve a pollution indicator of tundra biocenoses with polyarenes. The purpose of the present study is estimating the PAH distribution distance in the tundra zone under the impact of thermal power plant (TPP). The study was conducted in the Bolshezemelskaya tundra area of the Vorkuta region (Komi Republic, Russia). The surface accumulation and total content of PAHs in Pleurozium schreberi and organic horizon of tundra surfacegley soils (Stagnic Cambisols) at the background site and sites removed from the TPP at 0.5; 1; 1.5; 3; 5 and 12 km were studied. The PAH content in Pleurozium schreberi under the impact of TPP changes with distance not linearly. The maximum accumulation was noted at 3 km distance, then the content of PAHs decreased and reached a background level of 12 km from the source. The high molecular weight structures seemed to be transported at distance of no more than 3 km and fell down to the moss surface. The light structures could fly further. This fact responded for concentration of heavy and light structures on particles with different diameter. The moss surface at the background and polluted sites did not contain naphthalene. The total polyarene capacity on the moss surface is relatively the same for the background and polluted sites. At 3 km site, there was a sharp increase in the mass fraction of surface PAH by a factor of 3 due to an increase in the mass fraction of 4-5 - nuclear polyarenes. Being contaminated, the moss activates the bioaccumulation processes of PAHs and so transports polyarenes from its surface to inner organs. The exclusion is a site at a distance of 3 km where the proportion of surface accumulation increased with maximum pollution, i.e., PAH ingress into moss decreased. Determined that the dead part of Pleurozium schreberi or the whole plant is to be used for true identification of polyarenes. The changes in polyarene content in organic soil horizons are the same as in Pleurozium schreberi . By the obtained data, PAHs in tundra can move at large distances. The background-like PAH values are estimated for the site as 12 km from the pollution source for Pleurozium schreberi . The background-like PAH values for organic soil horizons are not estimated. The obtained results agree with the cluster analysis data.